PENGARUH PELATIHAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU MADRASAH ALIYAH NEGERI (MAN) DI KABUPATEN TANAH DATAR - Joni Roza (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
The purpose of this research was to reveal how extend the correlation of the training and the teaching experience toward the teachers’ performance of State Islamic High School in Tanah Datar. There were three hypotheses tested 1) the training contributed significantly toward the teachers’ professionalism; 2) the teachers’ teaching experience contributed significantly toward the teachers’ professionalism; 3) simultaneously, the training and teaching experience contributed significantly toward the teachers’ performance of State Islamic High School Tanah Datar. The research population were all teachers of State Islamic High School Tanah Datar which consist of 121 teachers and 53 teachers were selected as a research sample by using stratified proportional random sampling. Research data were collected through questionnaire. The first, and second hypothesis were tested by using simple correlation and regression, and the third hypothesis was tested by using multiple regression. The result showed that a) the training contributed significantly (26,50%) toward the teachers’ professionalism; b) the teachers’ teaching experience contributed significantly (26,00%) toward the teachers’ professionalism; and c) simultaneously, the training and the teaching experience contributed significantly (40,70%) toward the teachers’ professionalism. Keywords: Training, Teaching Experience, Teachers’ Professionalism, State Islamic High School, Tanah Datar